1994
DOI: 10.1126/science.8197456
|View full text |Cite
|
Sign up to set email alerts
|

Structure of the Allosteric Regulatory Enzyme of Purine Biosynthesis

Abstract: Multi-wavelength anomalous diffraction (MAD) has been used to determine the structure of the regulatory enzyme of de novo synthesis of purine nucleotides, glutamine 5-phosphoribosyl-1-pyrophosphate (PRPP) amidotransferase, from Bacillus subtilis. This allosteric enzyme, a 200-kilodalton tetramer, is subject to end product regulation by purine nucleotides. The metalloenzyme from B. subtilis is a paradigm for the higher eukaryotic enzymes, which have been refractory to isolation in stable form. The two folding d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
216
0
1

Year Published

1996
1996
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 265 publications
(221 citation statements)
references
References 43 publications
4
216
0
1
Order By: Relevance
“…While their catalytic mechanism and the amino acid residues surrounding the N-terminal nucleophile are strictly conserved, their substrate specificity has been shown to be quite broad, ranging from small hydrophilic or hydrophobic compounds to large proteins. Consequently, Ntn-hydrolases are utilized in a wide variety of cellular processes from protein degradation (26) to nucleotide biosynthesis (34). The discovery of PvdQ introduces yet another important role for Ntn-hydrolases, the hydrolysis of long acyl amides involved in quorum sensing.…”
Section: The Catalytic Mechanism Of Pvdq Proceeds Via a Covalently Boundmentioning
confidence: 99%
“…While their catalytic mechanism and the amino acid residues surrounding the N-terminal nucleophile are strictly conserved, their substrate specificity has been shown to be quite broad, ranging from small hydrophilic or hydrophobic compounds to large proteins. Consequently, Ntn-hydrolases are utilized in a wide variety of cellular processes from protein degradation (26) to nucleotide biosynthesis (34). The discovery of PvdQ introduces yet another important role for Ntn-hydrolases, the hydrolysis of long acyl amides involved in quorum sensing.…”
Section: The Catalytic Mechanism Of Pvdq Proceeds Via a Covalently Boundmentioning
confidence: 99%
“…Channeling processes are particularly advantageous over the free diffusion of reaction products through the bulk solvent because they can protect chemically labile intermediates from breakdown, prevent loss of nonpolar intermediates by diffusion across cell membranes, or protect the cell from toxic intermediates. Crystallographic studies on a number of different enzyme systems involved in substrate channeling (3)(4)(5)(6)(7)(8)(9)(10)(11) have revealed important structural factors that mediate intersubunit or interdomain communication and facilitate the efficient transfer of intermediates between distant active sites.…”
mentioning
confidence: 99%
“…GGT is a relatively recent addition to the Ntn-hydrolase superfamily (Suzuki & Kumagai, 2002). Many members of the Ntn-hydrolase superfamily have been structurally characterized, including B. subtilis glutamine 5-phosphoribosyl-1-pyrophosphate amidotransferase (Smith et al, 1994), E. coli penicillin G acylases and the E. coli, H. pylori and B. subtilis GGTs (Boanca et al, 2007;Okada et al, 2006;Wada et al, 2010). BLAST results suggested that HpxW is a member of the GGT family, which has modest sequence identity among its members ($30%; Suzuki et al, 1989).…”
Section: Comparison Of Hpxw To Other Enzymesmentioning
confidence: 99%